Respons Bibit Kopi Liberika terhadap Fungi Mikoriza Arbuskula, Cocopeat, dan Pupuk NPK pada Tanah Ultisol - Manurung, Ririn Elfrida; Radian, Radian; Sasli, Iwan (Politeknik Negeri Lampung, 2026)
Liberica coffee has great potential in West Kalimantan, but its productivity is low due to old plants that have not been rejuvenated. To improve yields, good planting media is needed, such as the use of arbuscular mycorrhizal fungi (AMF) and the addition of cocopeat. Proper NPK fertilization is also important soil. This study aims to observe the response of coffee seedlings to the application of mycorrhiza, cocopeat, and NPK fertilizer. The research was conducted in Limbung Village, Kubu Raya Regency, using a factorial completely randomized design with three factors. The first factor is mycorrhiza with two treatment levels, the second factor is cocopeat with four treatment levels, and the third factor is NPK fertilizer with three treatment levels. The results showed that the interaction treatment between mycorrhiza, cocopeat, and NPK fertilizer provided the best results, specifically the combination of mycorrhiza + 25 g. plant-1 cocopeat + 1 g.plant-1 NPK fertilizer on the growth of coffee seedlings in Ultisol soil, thereby accelerating seedling readiness for transplanting and field planting.